Traditional Malay medicine in Singapore : a gramscian perspective - Faizah Zakaria (2021)
Studies of Singapore’s brand of technocratic authoritarianism have generally focused on the political sphere. This article examines the social aspect of authoritarian hegemony by focusing on Singapore’s traditional Malay medicine (TMM) sector, which comprises a range of practitioners from shops offering herbal remedies to individuals specialising in Malay massage to spiritual healers. The transition in TMM’s position from the centre of the Malay community’s healing system to the periphery of the formal healthcare system parallels the process of authoritarian modernisation in Singapore. Applying a Gramscian analysis to this transition highlights the interplay between consensus and coercion in driving such social change. Using data gathered from in-depth, semi-structured interviews with current TMM practitioners and a survey of its users, this article further shows that far from being a set of static practices, TMM is dynamic and adaptable. Practitioners, who market their products along quasi biomedical lines, and consumers, who deconstruct their notion of the ‘healthy body’ by utilising traditional medicine to complement the biomedical, demonstrate this adaptability.